European Public Service Media, Disability Sports and Cultural Citizenship in the Digital Age: An Analysis of Agenda Diversity in the Tokyo 2020 Paralympic Games - Xavier Ramon; José Luis Rojas-Torrijos (Journalism and Media, 2023)
In the current cross-media ecosystem, which is characterized by technological disruption, the prominent relationship between public service media (PSM), sport and cultural citizenship is undergoing a profound transformation. Currently, PSM can utilize its myriad platforms, channels and services to transcend the constraints of linear broadcasting, find new ways of advancing diversity and overcome the perception of disability sport as a media ‘blind spot’. Through content analysis, the objective of this research has been to examine the agenda diversity on Twitter offered during the timeframe of the Tokyo 2020 Paralympic Games by 15 PSM corporations in Europe. This comparative analysis of 6072 tweets demonstrated the uneven attention devoted by European PSM to the Tokyo 2020 Paralympics. In the aggregate, 39.42% (n = 2398) of the messages focused on the event, although significant imbalances can be observed among the different media organizations, both in terms of the volume of coverage and the attention given to the various Paralympic disciplines and protagonists. From a theoretical perspective, the article adds to the existing literature on the nexus between media, sport and cultural citizenship, signaling the need for PSM to reimagine its social media strategies to counteract the limited visibility of different societal groups and to adequately contribute to enhancing cultural citizenship in the digital age. The results can also inform media practitioners. Despite that the conditioning factors and trade-offs linked to the commercial nature of social networking sites cannot be overlooked, PSM should take into account the importance of promoting inclusion and observe audiences’ increasing interest in disability sport.